Desarrollo de un marco de referencia para la gestión de realización de beneficios de proyectos (2017)
Organizations, regardless of their nature, size and object, seek to create value (not necessarily economic), which is why they define the vision, objectives and goals they want to achieve, as a result of market needs, obligations or requirements. Fulfill, the opportunities to be exploited, the problems they must solve or the particular interests of the investors or the interested parties. This organizational vision and strategic objectives, as well as their raison d'être (mission), make up the strategic planning or strategy of the organization, which together with the tactical and operative objectives are developed through the management or organizational direction of projects and the Routine and permanent operations. The management performed by an organization (projects and operations) seeks to create value for stakeholders, which is composed, on the one hand, of the value of the business and, on the other hand, for the positive impact or benefit that a population receives. Business value is defined as the total value of an organization, that is, the sum of the tangible and intangible elements that comprise it. The positive benefit or impact is the wealth or value that a population perceives through the use or access to a product or service, as well as the experience of a positive change or condition of the environment (public services, health, education, security, public transport Massive), which is derived from the realization of a public investment project, usually by the State or sponsored by the State. This degree work focuses on the management of realization of project benefits, understanding that it is through the management of projects, programs and portfolios, how organizations execute their strategy to achieve better results and competitive advantages in the market or the environment . The bibliographical research allowed to infer that the management of the projects from the different approaches analyzed focuses more on the generation of deliverables, products, services, results or changes, without formally taking care of the realization of benefits, which usually materialize during The phase of operation of the project product. This emphasis does not ensure that the project is successful and is forcing organizations to rethink their indicators as well as how to plan and execute projects that leverage business strategy. On the other hand, when organizations establish programs or portfolios they have a greater focus towards the benefits and the generation of value respectively, however; It is not clear what to do to manage the realization of benefits, in a project that is not part of a program, and is in a portfolio not formally defined. For this reason, the research group proposes as a solution a reference framework for the management of benefit realization of projects that are not part of a program, and are within a portfolio not formally defined. This frame of reference is made up of four processes: identification, planning, realization and sustainability. Also, this document provides a series of tools and templates that facilitate the understanding and appropriation of this complementary practice to the management of projects as it is currently conceived.